2018
DOI: 10.14715/cmb/2018.64.5.25
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of integron gene cassette arrays associated multi-drug resistant Enterobacteriaceae isolates from poultry

Abstract: The study investigated 110 Enterobacteriaceae isolates from broiler chickens isolated from Sharkia poultry farms and analyzed the isolates antimicrobial resistance and the presence of integrons as a potential basis for this resistance. Antibiotic susceptibilities against 12 different antibiotics were determined by the disk diffusion method. Prevalences and classes of integrons were then detected in multi-drug resistant (MDR) strains using polymerase chain reaction-restriction fragment length polymorphism (PCR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Antimicrobial resistance has developed widely as a result of the indiscriminate use of antimicrobial agents, which has gotten a lot of national and international attention [ 30 ]. The current resistance phenotypes with multidrug resistance (MDR) recorded in this study are similar to the data reported from another regional study [ 48 ] in Egypt as well as worldwide studies such as Halfaoui et al [ 46 ] in Algeria, Ibrahim et al [ 47 ] in Jordan, Singh et al [ 30 ] in India .…”
Section: Discussionsupporting
confidence: 88%
“…Antimicrobial resistance has developed widely as a result of the indiscriminate use of antimicrobial agents, which has gotten a lot of national and international attention [ 30 ]. The current resistance phenotypes with multidrug resistance (MDR) recorded in this study are similar to the data reported from another regional study [ 48 ] in Egypt as well as worldwide studies such as Halfaoui et al [ 46 ] in Algeria, Ibrahim et al [ 47 ] in Jordan, Singh et al [ 30 ] in India .…”
Section: Discussionsupporting
confidence: 88%
“…Antibiotic resistance can develop as a result of excessive antibiotic usage [ 3 , 42 , 43 ]. In this study, the antimicrobial resistance profile among Salmonella isolates was nearly similar to those recorded in Egypt [ 6 ], China [ 44 ], and Bangladesh [ 31 ].…”
Section: Discussionsupporting
confidence: 77%
“…Antibiotics have long been regarded as the primary tools for controlling Salmonella , helping farmers to improve the health and growth of their livestock. However, bacterial pathogens have created and disseminated a variety of antibiotic resistance mechanisms that can spread among microbial populations questioning the use of antibiotics [ 2 , 6 , 7 ]. As a result, Salmonellosis therapy has become more challenging due to antibiotic resistance, that has been linked to bacterial biofilm synthesis [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with the serological results reported by Abuelnaga et al . (2021 ) and El-Demerdash et al . (2018 ).…”
Section: Discussionmentioning
confidence: 97%